System Design of Three Phases Six Legs DC/DC Converter for Solar Cell - Muhammad Prihadi Eko Wahyudi; Qoriatul Fitriyah; Novie Ayub Windarko (Politeknik Negeri Batam, 2021)
this paper describes the design of full bridge DC to DC converter 3 phase six legs for solar PV. The prototype is built with 5 kHz transformers, 2 lead-acid batteries with each energy storage of 12V, 7.2Ah and 20WP solar PV. Three phase switching is provided by analog op-amp comparator circuit with variable frequency 1 kHz-20 kHz. The controller of the converter use adjustable DC power supply as voltage reference for analog op-amp comparator, works varies from 0-11VDC (0%-50% duty cycle) and controlled manually